-(-2b-9)=12(b-7)-7

Simple and best practice solution for -(-2b-9)=12(b-7)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-2b-9)=12(b-7)-7 equation:


Simplifying
-1(-2b + -9) = 12(b + -7) + -7

Reorder the terms:
-1(-9 + -2b) = 12(b + -7) + -7
(-9 * -1 + -2b * -1) = 12(b + -7) + -7
(9 + 2b) = 12(b + -7) + -7

Reorder the terms:
9 + 2b = 12(-7 + b) + -7
9 + 2b = (-7 * 12 + b * 12) + -7
9 + 2b = (-84 + 12b) + -7

Reorder the terms:
9 + 2b = -84 + -7 + 12b

Combine like terms: -84 + -7 = -91
9 + 2b = -91 + 12b

Solving
9 + 2b = -91 + 12b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-12b' to each side of the equation.
9 + 2b + -12b = -91 + 12b + -12b

Combine like terms: 2b + -12b = -10b
9 + -10b = -91 + 12b + -12b

Combine like terms: 12b + -12b = 0
9 + -10b = -91 + 0
9 + -10b = -91

Add '-9' to each side of the equation.
9 + -9 + -10b = -91 + -9

Combine like terms: 9 + -9 = 0
0 + -10b = -91 + -9
-10b = -91 + -9

Combine like terms: -91 + -9 = -100
-10b = -100

Divide each side by '-10'.
b = 10

Simplifying
b = 10

See similar equations:

| 3x^3+8x=10x^2 | | 0.4y=10 | | 120+22x=105-4x | | 2/9*3/4 | | 5x+1=5(x-6) | | 2/983/4 | | 2(x-2)=2x+6 | | 9x+5=4(2x-1)+9 | | 4(5x+3)+5=13x+3 | | -13+4x=-52+25 | | 3ax+12ax-36a=0 | | 4+91x=39x+12 | | (x+2)(x+5)=18 | | (3v-6)/3v | | .5(x+30)+1.1x=79 | | -(-2a-3)-5=-3(a-6) | | c^2d^2-4cd+4=0 | | -4(x+1)=-1(x+5) | | a^6-7a+a-7=0 | | 3(25-b)+b=35 | | x^3-7x^2+6=0 | | -2-(-8)-7+3= | | 9x^2-20x+2=0 | | -4k-(3-7k)=15 | | 4b-6b+7=9 | | 7=5c+22-10c | | 2w-7w+3=-22 | | 46=4x-4+6x | | -7w-(w+4)=12 | | 5(x-2)+3=-3(2x+1)-6 | | 7m+20-10=-25 | | 36r^2-60r+25=0 |

Equations solver categories